2023
DOI: 10.1021/acs.macromol.2c02307
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Radical Polymerization with Biocatalysts

Abstract: Reversible deactivation radical polymerization (RDRP) is a set of powerful and versatile methods for the synthesis of well-defined polymers. Over the past two decades, the engagement of biocatalysts, namely, enzymes and bacteria, has granted distinctive features to RDRP and propelled RDRP toward a more sustainable future. In this Perspective, we highlight the green conditions, oxygen tolerance, versatile function, and the ability to access difficult polymers in RDRP conducted by biocatalysis (bio-RDRP), discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…It is noteworthy to mention that other oxidase enzymes, such as horseradish peroxidase (HRP), pyranose oxidase (P2Ox), and formate oxidase (FOx), have also been successfully employed in enzyme catalysis mediated RAFT polymerization (Table 3). [53][54][55][56][57]…”
Section: Enzyme Catalysis-induced Raft Polymerizationmentioning
confidence: 99%
“…It is noteworthy to mention that other oxidase enzymes, such as horseradish peroxidase (HRP), pyranose oxidase (P2Ox), and formate oxidase (FOx), have also been successfully employed in enzyme catalysis mediated RAFT polymerization (Table 3). [53][54][55][56][57]…”
Section: Enzyme Catalysis-induced Raft Polymerizationmentioning
confidence: 99%
“…12 Extensive research has shown that enzymatic polymerization is a friendly strategy for the preparation of mechanically robust nanocomposite hydrogels. [13][14][15][16][17] HRP is a very popular and efficient bioenzyme that has been researched in the preparation of hydrogel. [18][19][20] In 1992, Derango et al conducted an initial study that demonstrated the application of HRP and other oxidase enzymes as catalysts for the polymerization of vinyl monomers by free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it holds great promise as a powerful technique for modern polymer chemistry with broader scope for materials researchers and pharmacists 44,45 and has been recently reviewed elsewhere. 46–48 In 2011, di Lena and co-workers documented enzyme-mediated free radical polymerization of methacrylic monomers in water by using an initiating system that resembles activators regenerated by electron transfer-ATRP (ARGET-ATRP). 49,50 The system is based on the metalloenzymes ( i.e.…”
Section: Introductionmentioning
confidence: 99%